Fasilitas Penunjang Industri Kain Endek di Kota Denpasar, Bali: bahasa indonesia - Muliadi Arisasmika Arsitektur; Ni Putu Ratih Pradnyaswari Anasta Putri; I Wayan Runa (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
For a city to thrive, it needs a Creative Hub, which can be a place for social interaction and communication between various groups. Creative Hubs function as dynamic areas that provide employment options, educational opportunities, corporate development opportunities, and networking opportunities. It also encourages more intensive innovation in the creative field for the benefit of the local community and region. In general, Creative Hubs are facilities or containers, both physical and virtual, that can connect communities or creative activists by providing a dynamic space so that new innovations and creativity can be born. Because of its nature as a center, the creative hub only covers part of the area. However, activities in the creative hub connect talents, skills, and disciplines in the creative community. Planning and Designing Creative Hub Facilities in Denpasar City, Bali can later become a support for the endek fabric industry in addition to the availability of other facilities that can support activities for creative industry players. So it is hoped that this design can be able to facilitate young people in Denpasar City and is expected to build and increase activities for creative economic actors who will produce products of economic value.